Broad‐spectrum inhibitory effect of green synthesised silver nanoparticles from Withania somnifera (L.) on microbial growth, biofilm and respiration: a putative mechanistic approach. Issue 3 (14th February 2018) - Abul Qais, Faizan; Samreen,; Ahmad, Iqbal
Abstract : Multi‐drug resistance in pathogenic bacteria has created immense clinical problem globally. To address these, there is need to develop new therapeutic strategies to combat bacterial infections. Silver nanoparticles (AgNPs) might prove to be next generation nano‐antibiotics. However, improved efficacy and broad‐spectrum activity is still needed to be evaluated and understood. The authors have synthesised AgNPs from Withania somnifera (WS) by green process and characterised. The effect of WS‐AgNPs on growth kinetics, biofilm inhibition as well as eradication of preformed biofilms on both gram‐positive and gram‐negative pathogenic bacteria was evaluated. The authors have demonstrated the inhibitory effect on bacterial respiration and disruption of membrane permeability and integrity. It was found that WS‐AgNPs inhibited growth of pathogenic bacteria even at 16 µg/ml. At sub‐minimum inhibitory concentration concentration, there was approximately 50% inhibition in biofilm formation which was further validated by light and electron microscopy. WS‐AgNPs also eradicated the performed biofilms by varying levels at elevated concentration. The bacterial respiration was also significantly inhibited. Interaction of WS‐AgNPs with test pathogen caused the disruption of cell membrane leading to leakage of cellular content. The production of intracellular reactive oxygen species reveals that WS‐AgNPs exerted oxidative stress inside bacterial cell causing microbial growth inhibition and disrupting cellular functions.